Analisis Strategi Pangkalan Militer Amerika di Korea Selatan: Proyeksi Kekuatan Regional dari Pengaruh Korea Utara - Arina Nihayati (Prodi Ilmu Hubungan Internasional, Universitas Fajar, 2024)
The United States and South Korea are strengthening security from regional threats coming from North Korea. The U.S. is building a military base in South Korea as a projection of strategic power in the region. As a superpower in terms of military and economic, America made various efforts to maintain its influence in the region. Based on this background, the US Department of Defense builds military bases in the region of Alliance countries with the aim of maintaining regional stability, balancing strategies, and maintaining peace. This study uses a neorealist approach and the concept of power projection in explaining the strategy of American military bases. As a result, the authors found the strategy of Loss of Strength Gradient is the projection of strength with the idea of the efficiency of military arrivals during the war to the enemy country. In addition, the military force projection strategy explains the deployment of concentrations of military bases in regions considered a state threat such as military bases in South Korea. The United States is trying to maintain its alliance on the Korean Peninsula due to security tensions between South and North Korea. Keywords: America; Military Base; Strategy; South Korea; North Korea